MODELLING OF WEAR ON A CIRCULAR CAM PROFILE - Keskin, Ilknur; Bozaci, Atilla (YILDIZ TECHNICAL UNIV, 2012)
Life prediction for dynamic systems is very important for machine designers in terms of technical and economical reasons. Wear of co-working surfaces is a critical factor affecting the life of the product. Although wear is definitely an ordinary event, the mechanism and theory of wear are very complex phenomenon of the system which includes material properties, operating conditions (load, speed, etc.), contact geometry, surface roughness, and environment (lubrication, temperature, etc.). However, it is not possible to deal with so many components on a mathematical model. The modelling studies which involves the wear arised surface of the cam by considering only spring forces effects are present in the literature. In this study, the mathematical model has been formed by considering inertia forces arising from the spring affecting cam mechanism and acceleration of the follower. Archard's wear equation has been adapted to the current situation and a mathematical model which reveals the depth of wear depending on the force and time variable has been established in dry conditions. For the same existing conditions, experimental studies have been performed for PTFE cam profile and then wear depth of the worn cam profile have been determined by CMM (Coordinate Measuring Machine) for different angles. Experimental results were compared with the theoretical data that as a mathematical model put forward and was seen a reliable modelaccording to the amount of wear estimated, and new cam and follower profiles are obtained.
Keywords: Cam; follower; wear; wear coefficient; CMM; Engineering